Studi awal rancang bangun colorimeter sebagai pendeteksi pada pewarna makanan menggunakan sensor photodioda (Early studies on the design of a colorimeter to detect food coloring using a photodiode sensor ) - Delvi Ayu Wulandari; - Yulkifli (Department of Physics – Universitas Negeri Padang UNP, 2018)
Laboratory have a function important in research. Laboratory of science must be have instrumentation who sophisticated. Chemistry not separated from research, one of the research of chemistry is colorimetric. Colorimetric is a method used in chemical analysis. The method of colorimetric is used intensity of solution. The instrumentation who measuring intensity of solution is colorimeter. This research is make colorimeter used sensor photodiode. Sensor photodiode is photo detector and very sensitivity to radiance. The sample of research is food dye. The food dye in this research is green. The chosen of food dye causes the sensor just can detection color of green. The result showed the measurement of average output voltage is 1,378 V. The output sensor not stable cause the sensor have high sensitivity. Desain of instrument colorimetric is a black box. The Selection of black box cause the measurement result are not affected by external light. The research light source is monochromatic.